Flavin reductase: sequence of cDNA from bovine liver and tissue distribution. - Quandt, K S (1994)
Flavin reductase catalyzes electron transfer from reduced pyridine nucleotides to methylene blue or riboflavin, and this catalysis is the basis of the therapeutic use of methylene blue or riboflavin in the treatment of methemoglobinemia. A cDNA for a mammalian flavin reductase has been isolated and sequenced. Degenerate oligonucleotides, with sequences based on amino acid sequences of peptides derived from bovine erythrocyte flavin reductase, were used as primers in PCR to selectively amplify a partial cDNA that encodes the bovine reductase. The template used in the PCR was first strand cDNA synthesized from bovine liver total RNA using oligo(dT) primers. A PCR product was used as a specific probe to screen a bovine liver cDNA library. The sequence determined from two overlapping clones contains an open reading frame of 621 nucleotides and encodes 206 amino acids. The amino acid sequence deduced from the bovine liver flavin reductase cDNA matches the amino acid sequences determined for erythrocyte reductase-derived peptides, and the predicted molecular mass of 22,001 Da for the liver reductase agrees well with the molecular mass of 21,994 Da determined for the erythrocyte reductase by electrospray mass spectrometry. The amino acid sequence at the N terminus of the reductase has homology to sequences of pyridine nucleotide-dependent enzymes, and the predicted secondary structure, beta alpha beta, resembles the common nucleotide-binding structural motif. RNA blot analysis indicates a single 1-kilobase reductase transcript in human heart, kidney, liver, lung, pancreas, placenta, and skeletal muscle.